The Membrane Interface dictates Different Anchor Roles for “Inner Pair” and “Outer Pair” Tryptophan Indole Rings in Gramicidin A Channels - Gu, Hong (2011)
We investigated the effects of substituting two of the four tryptophans (the “inner pair” Trp(9,11) or the “outer pair” Trp(13,15)) in gramicidin A (gA) channels. The conformational preferences of the double-substituted gA analogues were assessed using circular dichroism spectroscopy and size-exclusion chromatography, which show that the inner tryptophans 9 and 11 are critical for the gA’s conformational preference in lipid bilayer membranes. [Phe(13,15)]gA largely retains the single-stranded helical channel structure, whereas of [Phe(9,11)]gA exists primarily as double-stranded conformers. Within this context, the (2)H-NMR spectra from labeled tryptophans were used to examine the changes in average indole ring orientations, induced by the Phe substitutions and by the shift in conformational preference. Using a method for deuterium labeling of already synthesized gAs, we introduced deuterium selectively onto positions C2 and C5 of the remaining tryptophan indole rings in the substituted gA analogues for solid-state (2)H-NMR spectroscopy. The (least possible) changes in orientation and overall motion of each indole ring were estimated from the experimental spectra. Regardless of the mixture of backbone folds, the indole ring orientations observed in the analogues are similar to those found previously for gA channels. Both Phe-substituted analogues form single-stranded channels, as judged from the formation of heterodimeric channels with the native gA. [Phe(13,15)]gA channels have Na(+) currents that are ~50% and lifetimes ~80% those of native gA channels. The double-stranded conformer(s) of [Phe(9,11)]gA do not form detectable channels. The minor single-stranded population of [Phe(9,11)]gA forms channels with Na(+) currents that are ~25% and single-channel lifetimes that are ~300% those of native gA channels. Our results suggest that Trp(9) and Trp(11), when “reaching” for the interface, tend to drive both monomer folding (to “open” a channel) and dimer dissociation (to “close” a channel). Furthermore, the dipoles of Trp(9) and Trp(11) are relatively more important for the single-channel conductance than are the dipoles of Trp(13) and Trp(15).